(untitled) (Педагогіка вищої та середньої школи, 2009)
In the article the author expresses essence of personality’s self affirmation, explains maintenance and principles of construction the programme of development a personality of senior pupil From self-affirmation to self-realizations which is a theoretico-methodological base for a conscious management students by their development.